Menggali Literasi Keuangan pada Masyarakat Penerima Bantuan Keluarga Harapan (PKH) di Desa Kediri Induk - Sukriati Sukriati (CV. ULIL ALBAB CORP, 2024)
This study aims to determine the financial literacy of the community receiving family hope assistance (PKH) in Kediri Induk Village, West Lombok Regency, NTB, Financial literacy in this study is seen from a person's knowledge of the value of an item and the priority scale in his life, budgeting, savings, how to manage finances, credit management, and the basics of investment. The beneficiaries are poor people with uncertain incomes so they have to manage their finances well to achieve prosperity and not only rely on assistance from the government.This research uses qualitative methods - descriptive research data in the form of data from the community receiving aid, interview results, notes from interviews and documentation in the form of photos when the research was carried out. Data analysis in this research (qualitative) starts from data reduction, data presentation and drawing conclusions.Based on the results of the research conducted, it was found that financial literacy in the people of Kediri Main village, West Lombok Regency was owned by seven respondents, three of whom were able to manage their finances well.